Pengaruh Model Pembelajaran Picture And Picture Terhadap Hasil Belajar Siswa di SMP Negeri 02 Kota Bengkulu - Rossa Ayuni; Reiza Adriyani (Universitas Dehasen Bengkulu, 2022)
This study aims to: Knowing how the application of the Picture and Picture learning model to student learning outcomes at SMP Negeri 02 Bengkulu City. This type of research is a quasi-experimental research. The samples of this study were students of class 7a and 7b of SMP Negeri 02 Bengkulu City. The technique used in sampling is purposive sampling. The techniques used in data collection are observation, test and documentation. The data analysis technique used t-test. The results of this study indicate that: Picture and Picture learning model has an influence on student learning outcomes at SMP Negeri 02 Bengkulu City with a percentage increase of 64%.